2015
DOI: 10.5935/medicalexpress.2015.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic modulation adjustments in isometric exercise

Abstract: OBJECTIVE: Isometric exercise is characterized by promoting an overload on the cardiovascular system due to pulsatile contraction followed by a significant increase in muscle blood flow. The hemodynamic responses during exercise and during recovery from endurance exercise are well documented. However, there are few studies with hard data regarding the influence of isometric exercise on autonomic control, which can be obtained by analysis of heart rate variability. Thus, the object of this study was to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Historically, isometric exercise has been avoided for clinical populations due to a hypothetical sudden increase in BP inducing arrhythmia 7 . Nonetheless, in the last decades, a plethora of evidence suggests that IHE modulates cardiac autonomic function, playing an important role in hemodynamic stability 8,13,14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, isometric exercise has been avoided for clinical populations due to a hypothetical sudden increase in BP inducing arrhythmia 7 . Nonetheless, in the last decades, a plethora of evidence suggests that IHE modulates cardiac autonomic function, playing an important role in hemodynamic stability 8,13,14 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, IHE might play an important role in cardiac autonomic function, one of the main cardiovascular concerns in HD patients 11,12 . Different from other types of exercise, such as aerobic, resistance, and combined that promote musculoskeletal and cardiorespiratory benefits, IHE main focus is in the sympathetic‐parasympathetic modulation 4,6,9,13 …”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear behavior of HRV during recovery from exercise was explored in previous studies. [11][12][13][14][15] Mendonça et al 32 analyzed nonlinear behavior of HRV during recovery from a supramaximal exercise period. The study established: (a) a significant increase in alpha-1 scaling component of detrended fluctuation analysis (DFA) after exercise in healthy men and women and (b) a positive correlation with LF/HF ratio, indicating decreased chaotic behavior of HRV associated with elevated sympathetic cardiac modulation after exercise, which uphold our analysis here.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It may be hypothesizedthat reduced sympathetic and increased parasympathetic nervous system activity and activation of the BezoldJarish, are involved in the response observed in our study. In this context, the Bezold-Jarish reflex is a sympatho-inhibitory cardio depressor reflex, which present important role in cardiovascular homeostasis [13,19].Previously, von Bezold and Hirt observed that an intravenous injection of veratrum alkaloids caused a decrease in blood pressure and heart rate, which was then named the Bezold-Jarisch reflex or cardiopulmonary reflex [21].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the sympathetic activation did not significantly influence the cardiac autonomic modulation in hemodynamically stable patients with renal disease and that the increase in the global modulation of the heart occurred as a response to the initial activation of the sympathetic nervous system. This initial response of the autonomic nervous system activation is presented with cardiac protective as tonic response of the autonomic reflexes in order to stabilize cardiac functions promoting improved global functions during and after hemodialysis [18][19][20].…”
Section: Discussionmentioning
confidence: 99%